Hepatoprotective Phenolic Glycosides from Gymnema tingens - Tian, Jin; Ma, Qin-Ge; Yang, Jian-Bo; Wang, Ai-Guo; Ji, Teng-Fei; Wang, Yan-Gai; Su, Ya-Lun (Planta Medica, 2013)
Six new phenolic diglycosides, named gymnetinosides A–F (1–6), were isolated from the ethanolic extract of Gymnema tingens, together with three known diglycosides, sequinoside K (7), khaephuoside B (8), and albibrissinoside A (9). The structures of the new compounds were determined by spectroscopic techniques including 1D-, 2D NMR, mass spectroscopy, and circular dichroism. Compounds 1, 5, and 6 showed hepatoprotective activities against D-galactosamine-induced HL-7702 cell damage.
Keywords: Asclepiadaceae; Gymnema tingens; phenolic glycosides; hepatoprotective; structure elucidation